Ameliorative iron-deficiency anemia levels using natural orange juice and fortified with different concentrations of mango, strawberries and beetroot juices in male albino rats - Abdulmaguid, Nabila Mahmoud (Journal of natural sciences, life and applied sciences, 2018)
Iron deficiency anemia is the most prevalent type of anemia all over the world. It occurs as a result of iron malabsorption or low supply from food. This research aimed to study the role of natural orange juice and fortified with different concentrations of mango, strawberries and beetroot juices on anemic rats. Juices chemical composition was determined. Sensory characteristics were evaluated for different concentrations of juices. Male Albino rats were used to study the nutritional effect of juices on biological evaluation, hematological and biochemical analysis. The results showed increase the ratio of macro and micro nutrients, especially minerals in fresh orange juice, which is fortified by mango, strawberry and beetroots juices. Also, sensory characteristics of juice have improved. Biological evaluations as feed intake, body weight gain, feed efficiency ratio, and internal organ weight were also increased. The levels of complete blood count, serum protein, ferritin, iron and zinc were incremented. The study confirms the importance of possible using orange juice fortified with fresh fruit and vegetables juices to treatment iron deficiency anemia as a safe way of beings.
Keywords: biological evaluation; biochemical analysis; complete blood count; chemical composition; sensory characteristics